Targeting the key cholesterol biosynthesis enzyme squalene monooxygenasefor cancer therapy - Zou, Yuheng; Zhang, Hongying; Bi, Feng; Tang, Qiulin; Xu, Huanji (Frontiers in Oncology, 2022)
Cholesterol metabolism is often dysregulated in cancer. Squalene monooxygenase (SQLE) is the second rate-limiting enzyme involved in cholesterol synthesis. Since the discovery of SQLE dysregulation in cancer, compelling evidence has indicated that SQLE plays a vital role in cancer initiation and progression and is a promising therapeutic target for cancer treatment. In this review, we provide an overview of the role and regulation of SQLE in cancer and summarize the updates of antitumor therapy targeting SQLE.